Peran Guru Dalam Menciptakan Komunikasi Efektif Pada Anak Usia 4-5 Tahun - Pupung Puspa Ardini; Yenti Juniarti; Lowisa Yeblo (Student Journal of Early Childhood Education, 2023)
What is the role of the teacher in creating effective communication in early childhood 4-5 years at Ki Hadjar Dewantoro State Kindergarten, Kota Selatan District, Gorontalo City. Thesis Results of the Department of Teacher Education, Early Childhood Education, Faculty of Education, State University of Gorontalo. The formulation of the problem in this study is "What is the Role of the Teacher in Creating Effective Communication in Early Childhood 4-5 Years at Ki Hajar Dewantoro State Kindergarten, Kota Selatan District, City of Gorontalo” The purpose of this study was to examine the role of the teacher in creating effective communication in early childhood 4-5 years at Ki Hadjar Dewanto State Kindergarten, South City, Gorontalo City. "This research uses qualitative methods obtained through observation, analysis, interviews and data collection. So that researchers can conclude "That the role of the teacher is very important in creating effective communication for aspects of early childhood development, because the teacher is the role of facilitator, evaluator, mtivator and administrator in shaping the character and soul of children, by educating, nurturing, and teaching and directing children better